Reflecting on pain management for patients with osteoarthritis and other rheumatic disorders: there's more to pain management than managing pain. (July 2013) - Perret, Danielle; Chang, Eric Y; Pang, Winnie; Shinada, Shuntaro; Panush, Richard S
SUMMARY Medical progress is measured by advances in science and technology. The pace of discovery will surely accelerate. We are increasingly challenged not only to assimilate new information, but also to reconcile our learning with our art. We present the common clinical problem of managing pain in osteoarthritis as a paradigm for this dilemma in contemporary patient care. We do not yet have the understanding and interventions to do this optimally for all with osteoarthritis, leaving us with uncertainties as we struggle to care for these patients. In a world of growing complexity and sophistication we must not overlook the person who is our patient. It is easy to be seduced by electronic and informational advances, to be entranced by machinery, and to forget the unique individuality and needs of each patient. Osler taught that "the practice of medicine is an art, based on science". This doesn't change.